2018
DOI: 10.1039/c8nr01451e
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lanthanide-doped upconverting nanoparticles on cancer cell biomarkers

Abstract: Lanthanide-doped upconverting nanoparticles (Ln-UCNPs) possess optical and physicochemical properties that are promising for the design of new theranostic platforms. This applies in particular to the treatment of cancer. Towards this goal, oleate-capped-NaLuF4:Tm3+(0.5%)/Yb3+(20%)/Gd3+(30%) with an average size of 35 nm ± 2 nm were synthesized by co-precipitation. Due to their hydrophobic surface, these Ln-UCNPs produced agglomerates under cell culture conditions. To assess the cellular response to Ln-UCNPs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Indeed, a recent in vitro study reported a targeted killing of tumor cells by affecting specific tumor markers such as EGF by Ln-UCNPs. 87 Overall, these findings identify a potential use of UCNPs in colorectal cancer diagnosis and treatment.…”
Section: Detection and Treatment Of Colon Cancer By Ucnpsmentioning
confidence: 82%
“…Indeed, a recent in vitro study reported a targeted killing of tumor cells by affecting specific tumor markers such as EGF by Ln-UCNPs. 87 Overall, these findings identify a potential use of UCNPs in colorectal cancer diagnosis and treatment.…”
Section: Detection and Treatment Of Colon Cancer By Ucnpsmentioning
confidence: 82%
“…Later in stage three, the α‐phase begins to transform into the β‐phase, followed by ripening and finally particle growth in stage four. [ 59 ] More recently, the high‐temperature co‐precipitation method has been used in the synthesis of a wider range of UCNPs: including NaYF 4 , [ 60 ] NaLuF 4 , [ 61 ] LiYF 4 , [ 62 ] KLu 2 F 7 , [ 63 ] NaGdF 4 , [ 64 ] NaYbF 4 , [ 65 ] LiYbF 4 , [ 66 ] and KSc 2 F 7 . [ 67 ] With proper optimization of the conditions, uniform 4 nm NaREF 4 UCNPs with enhanced upconversion luminescence could be achieved.…”
Section: Synthesis Approaches In Batch Reactorsmentioning
confidence: 99%
“…Even though the relationship between optical performance and morphology of UCNPs have had been well understood, [ 23–26 ] relevant developments on commercializing such nanomaterials are hampered due to scaling‐up production process, where bottlenecks normally exist in the reproducibility, repeatability as well as the yield from these methods. By recapping these reported synthesis methods, for example, thermal decomposition, [ 35–40 ] co‐precipitation, [ 60–66 ] hydrothermal, [ 73–78 ] and ion exchange, [ 98–101 ] a common characteristics is discovered that these processes require large amounts of solvents, which easily lead to nonuniform precursor concentrations and temperature distributions. This characteristic represents an essential challenge in managing thermodynamic equilibrium for a smooth and uniform synthesis in lab, [ 27,28 ] and the scale‐up process where the breaking of local thermodynamic equilibrium is likely to occur to yield the uncontrollable changes on the phases and other features for the particle, especially the luminescent performance.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, UCNPs have a low specific surface area, no porous structure or functional groups, so UCNPs cannot carry drugs. In order to achieve the function of drug loading, hollow UCNPs are designed and the huge interior cavities of lanthanide‐doped hollow UCNPs can be hopefully applied as drug carrier …”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the function of drug loading, hollow UCNPs are designed and the huge interior cavities of lanthanide-doped hollow UCNPs can be hopefully applied as drug carrier. [17] Taking the photoluminescence advantages, Tm 3+ has received considerable attention as an activator of codoped upconversion nanoparticles. Due to similar chemical properties, Gd 3+ can be easily doped in the lattice of NaYF 4 :Yb,Tm nanocrystals.…”
Section: Introductionmentioning
confidence: 99%